2004
DOI: 10.1007/s10384-003-0006-2
|View full text |Cite
|
Sign up to set email alerts
|

Sclerosing Sweat Duct Carcinoma of the Eyelid

Abstract: This tumor is seldom recognized and is frequently confused with benign syringoma or inflammation. Wide and deep excisional biopsy is necessary for correct diagnosis and successful treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Review of the literature identified 92 patients fulfilling the inclusion criteria for this study in addition to our current patient, for a total of 93 patients with MAC. 2,3,5,8,9,11–69 Patient demographics and presenting characteristics are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Review of the literature identified 92 patients fulfilling the inclusion criteria for this study in addition to our current patient, for a total of 93 patients with MAC. 2,3,5,8,9,11–69 Patient demographics and presenting characteristics are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Additional interventions included simple re-excision (11/34, 32%) 2,5,11,15,24,29,40,57,66 with positive margins in 4 of 11 (36%) 5,24,66 of these cases and excision with frozen section clearance of margins (3/34, 9%). 2,5,40 Mohs micrographic surgery was performed in 13 of 34 (38%) 3,5,8,13,14,21,24,45,46,49 patients with known information. 3,13,24,49 Of these 13 cases, 2 were handled with a staged Mohs excision.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most frequently madarosis is observed in patients with leprosy, where it has been reported in 27–76% of cases (Hogeweg & Leiker 1983; Soshamma & Surayawanshi 1989; Dana et al 1994; Cakiner & Karacorlu 1998; John & Daniel 1999). Madarosis is also frequently found in patients with malignomas or as paraneoplastic syndrome (Leib et al 1991; Saghari et al 2002; Kodama et al 2004). Further frequent causes of madarosis are endocrinological disorders or intoxications (Roy 1997).…”
Section: Discussionmentioning
confidence: 99%
“…[1111113119120] A sebaceous cell carcinoma very often presents as a recurrent chalazion. An associated madarosis (due to lid infiltration and follicle destruction) would help to differentiate the two.…”
Section: Toxicitymentioning
confidence: 99%